Eyewitness to Early Reform in Myanmar - Wilson, Trevor (ANU Press, 2016)
By 2000, a ruthless military regime had ruled Myanmar for more than a decade, polarising opinion inside and outside Burma/Myanmar - with Western countries locked into non-UN sanctions and Asian countries and the rest of the world locked into unenthusiastic cooperation with Myanmar. While the United Nations and its agencies faced numerous obstacles as they sought to encourage national reconciliation in Myanmar, conditions in Myanmar were slowly starting to change. With a reform faction in charge, the military regime itself after 1999 slowly began experimenting with modest changes, before committing in 2008 to transfer power via a constitutional referendum and national elections, both of which it effectively controlled. This book provides the first eyewitness account of the early reform experiments.